Formulasi Pasta Gigi Bromelain Kasar Dari Batang Nenas (Ananas comosus L. Merr Var Queen) Sebagai Pembersih Gigi - Fifi Harmely (STIFARM Padang, 2009)
The studies about formulating toothpaste of crude bromelain from steams of pineapple (Ananas comusus L. Merr Var Queen) as cleaner of teeth have been done. Concentration of crude bromelain were used 3 %, 5 %, and 7 % respectly. The parameter evaluated conclude organoleptic observation, homogenity, pH, particle size distribution, spread test, foam test, preference test with panelist, and affectivity test with O.H.I.S (Oral Hygiene Index Simplified) Methods. The result showed that toothpaste Fl [3 %] has given best result based on physic evaluated and preferences test of panelist. The affectivity test as cleaner of teeth with O.H.I.S (Oral Hygiene Index Simplified) methods has given by toothpaste F3 [7 %].